Simulation of Propeller Runner for Cylindrical Basin of Gravitational Water Vortex Power Plant - Pandey, Shankar Nath; Chaulagain, Raj Kumar; Pandey, Bimal (Advances in Engineering and Technology: An International Journal, 2022)
The gravitational water vortex power plant is an emerging technology of power generation from water vortex in a small amount. It can generate electricity in a low head of range (0.7-2m). This system is very simple and requires less keep-up. This research aims to develop the propeller type runner which gives optimum efficiency and cylindrical basin suitable for this propeller runner in GWVPP. The research has been conducted by developing a new propeller runner and cylindrical basin considering the top surface open as the atmosphere. Blade angle, discharge hole diameter of the basin, the position of runner, and rpm are optimized on CFD-based optimization. After the CFD analysis, the optimum blade angle was 43º, exit hole diameter of this basin was found 175 mm which is 20% of the basin diameter. The optimum height was found 785mm which is 65.42% of the total height. And the efficiency of the optimized system was 23.639 % at 40 rpm.